Library and information science trends and research : Asia-Oceania - Spink, Amanda; Singh, Diljit (Library and information science (New York, N.Y.), 2012)
This book brings together a range of chapters about the trends in education and research in the field of library and information science (LIS) in the Asia-Oceania region of the world. Why a book about LIS in the Asia-Oceania region? One key reason for a book on the topic is the huge growth of the field in terms of students and schools particularly in Asia. Information is an important part of the human condition and critical to the development of the Asia-Oceania region.